LQ-moments: parameter estimation for kappa distribution - Ani Shabri,; Abdul Aziz Jemain, (Universiti Kebangsaan Malaysia, 2010)
Identification of the true statistical distributions for various hydrologic data sets is a major problem facing engineers. The four-parameter kappa distribution is a combination of the established distribution including the Generalised Extreme Value (GEV), Generalised Logistic (GL), Generalised Pareto (GP) and the Gumbel distribution were considered in this study. The main objective of this study was to develop the method of LQ-moments for the kappa distribution. The performance of the LQ-moments was compared with L-moments through eight problems using published data sets. The results show that the performance of both methods, the LQ-moments and L-moments worked equally well.